2018
DOI: 10.1093/jac/dky132
|View full text |Cite
|
Sign up to set email alerts
|

Insights about minority HIV-1 strains in transmitted drug resistance mutation dynamics and disease progression

Abstract: Transmitted drug resistance mutations representing small percentages of the viral population do not persist during infection because they are negatively selected in the first year after HIV-1 seroconversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Additional articles were identified by experts in the field. We screened out 1330 studies after removing duplicates, and 140 articles were downloaded for full-length screening, of which 39 articles were kept [ 6 , 17 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional articles were identified by experts in the field. We screened out 1330 studies after removing duplicates, and 140 articles were downloaded for full-length screening, of which 39 articles were kept [ 6 , 17 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…We recognize that a more detailed analysis of HIV quasispecies in this study would greatly benefit from single-genome amplification or next-generation sequencing tools. It has recently been demonstrated using next-generation sequencing (NGS) that transmitted drug-resistance mutations representing small percentages of the viral population do not persist during infection because they are negatively selected in the first year after HIV-1 seroconversion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the PI codons on the IAS list, we initially had data on 22. These were codons 10, 20, 24,30,32,36,46,47,48,50,53,54,63,71,73,77,82,84,85,88, 89, 90, and 93. We eliminated codons 32, 47, and 50 from our analysis as they either had 0 or 1 tests that showed that mutation and therefore did not allow comparison.…”
Section: Protease Inhibitor (Pi) Mutations At Dna Levelmentioning
confidence: 99%
“…We recognize that a more detailed analysis of HIV quasispecies in this study would greatly benefit from single genome amplification or next-generation sequencing (NGS) tools. It has been recently demonstrated using NGS that transmitted drug resistance mutations representing small percentages of the viral population do not persist during infection because they are negatively selected in the first year after HIV-1 seroconversion [48]. In this context, a recent study exploring the extinction dynamics of transmitted drug resistance mutations using next-generation sequencing showed that these mutations are rare at a 20% threshold of detection [49].…”
Section: M184v As a Special Case Of Mutationmentioning
confidence: 99%